Potential evaluation oil palm frond juice for bioethanol fermentation - Dhiyatul Ridhwan, Md Nasarudin (2013)
The fossil fuels degrade abundantly since 21st century. The usages of fossil fuels tend to emit the greenhouse gases that effect to global warming as well human health. To overcome these problems, the bioethanol introduced by the researches to substitute the fossil fuels. Bioethanol is a bioenergy produced by yeast fermentation at several conditions compared to conventional fossil fuels. Bioethanol is being studied because the unique properties and renewable fuels. The production of bioethanol in industrial scale involved high cost due to the usage of foods as sugar raw materials. Thus, this research is to evaluate the oil palm frond (OPF) juice as raw material for bioethanol fermentation. In this study, the bioethanol produces in shake flask by using Saccharomyces cerevisiae and OPF juice as medium component. Three parameters study are initial pH of medium, agitation speed, and OPF juice concentration. The best condition of parameters determine by the highest ethanol concentration produce. Inoculum prepared in shake flask to cultivate the yeast in medium growth and ferment in 250 ml shake flasks containing medium growth and beef extract. The flasks incubate in 48 hours, 12 hours interval for sample withdraw. The products analyse for sugar concentration and bioethanol concentration. The expected results for the best condition in bioethanol fermentation are in pH 7, 150 rpm agitation speed and 100% volume percentage of OPF juice concentration